Case Report: Active tuberculosis infection in CAR T-cell recipients post CAR T-cell therapy: a retrospective case series - Zhang, Peiling; Huang, Liang; Zheng, Miao; Zhang, Chao; Wan, Dongyi; Wei, Jia; Cao, Yang (Frontiers in Cellular and Infection Microbiology, 2023)
Chimeric antigen receptor (CAR) T-cell therapy has yielded high response rates in B-cell malignancies. Emerging reports demonstrate that the risk of active tuberculosis (TB) in the novel immunotherapy of tumor. However, studies of TB infection in patients post CAR T-cell therapy are limited. In this series case study, we presented five patients of active TB infection post CD19/CD22 target CAR T-cell therapy alone or following autologous stem cell transplantation (ASCT). One of the patients manifested as active TB infection within the first 30 days post CAR-T cell therapy and fever was the dominant presenting symptom, while extrapulmonary manifestations of active TB infection were common in other four of patients manifested after the first 30 days of CAR-T cell therapy. Four of five patients improved after anti-TB infection in this study, but one died of central nervous system TB infection with isoniazid resistance. Our study provides the first series report of the active tuberculosis after CD19/CD22 target CAR T-cell therapy.